2013
DOI: 10.1103/physrevb.87.024110
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field-crystal study of grain boundary premelting and shearing in bcc iron

Abstract: We use the phase-field-crystal (PFC) method to investigate the equilibrium premelting and nonequilibrium shearing behaviors of [001] symmetric tilt grain boundaries (GBs) at high homologous temperature over the complete range of misorientation 0 < θ < 90 • in classical models of bcc Fe. We characterize the dependence of the premelted layer width W as a function of temperature and misorientation. In addition, we compute the thermodynamic disjoining potential whose derivative with respect to W represents the str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 90 publications
(168 reference statements)
4
64
0
Order By: Relevance
“…In this case, a full analytical calculation of the disjoining potential is not possible anymore and numerical investigations are needed 33 . Nevertheless, we have explained that the interaction then stems from higher order terms in the free energy functional, since the longest-range contributions from quadratic terms cancel.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In this case, a full analytical calculation of the disjoining potential is not possible anymore and numerical investigations are needed 33 . Nevertheless, we have explained that the interaction then stems from higher order terms in the free energy functional, since the longest-range contributions from quadratic terms cancel.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A repulsive interaction, V (W ) < 0, typical for large misorientations, gives raise to grain boundary premelting, whereas attractive interactions, V (W ) > 0, stabilise a dry grain boundary. While combinations of these two cases with extrema in the disjoining potential can occur and result from the structure of V (W ) as being a superposition of exponentially decaying contributions with different ranges [3][4][5], we focus here on the elementary case of monotonic disjoining potentials.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Grain boundary premelting was investigated recently e.g. in [3][4][5][6], showing that for low misorientation an attractive interaction between adjacent solid-melt interfaces can stabilise a grain boundary. Recent investigations of heterogeneous nucleation of liquid droplets in overheated grain boundaries link the short range interactions to nucleation processes [7].…”
Section: Introductionmentioning
confidence: 99%
“…For small deformations this energy change is quadratic, hence linear elasticity is captured, and for larger deformations non-linear effects appear 9,10 . Whereas the original PFC model is fully phenomenological, later extensions have shown that it can be linked to the classical density functional theory of freezing [11][12][13] , which allows to determine the model parameters from fundamental physical quantities, which can for example be determined from molecular dynamics simulations [14][15][16][17] . The obtained elastic constants can then be obtained from properties of the liquid structure factor and give reasonable estimates of the high temperature values near the melting point.…”
Section: Introductionmentioning
confidence: 99%